Pengaruh Model Problem Based Learning Berbantuan Crossword Puzzle terhadap Hasil Belajar IPAS Kelas IV SD - Elza Nanda; Susanti Murwitaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to determine the effect of problem-based learning with the help of crossword puzzles on student learning outcomes. This model is applied to IPAS lessons, especially social studies to increase interest and understanding in the material of buying and selling activities as a fulfillment of needs through keywords. The method used was a quasi-experiment with a nonequivalent control group design. The population of this study were all fourth grade students of SDN Batu Ampar 02 in the 2023/2024 school year, totaling 126 students. The research sample consisted of 62 students, consisting of two groups where class IV A as the experimental group and class IV D as the control group, each class numbered 31 students. Data on learning outcomes were obtained through pre-test and post-test, tests in the form of multiple choice questions. Data analysis using t-test for independent samples. Based on the research results, hypothesis testing shows a significant value of 0.000 <0.05 which means H0 is rejected, therefore it can be concluded that the problem-based learning model assisted by crossword puzzles has an influence on the learning outcomes of IPAS on grade IV students at SDN Batu Ampar 02.